Disease‐ and treatment‐related expectations, attitudes, and beliefs among adult patients initiating or switching biological therapies for psoriasis - Maria Clemmesen; Astrid‐Helene Ravn Jørgensen; Valdemar Wendelboe Nielsen; Nikolaj Holgersen; Christoffer Valdemar Nissen; Jacob Pontoppidan Thyssen; Alexander Egeberg; Simon Francis Thomsen (JEADV Clinical Practice, 2023)
Abstract Background The treatment expectations of patients with psoriasis are essential for clinical outcomes. Objectives To examine disease‐ and treatment related intra‐ and interpersonal factors and their relation to treatment expectations among patients with psoriasis who initiate or switch biological therapy. Methods Consecutive adult patients with moderate to severe psoriasis who initiated or switched biological therapy completed a questionnaire regarding their disease‐ and treatment‐related expectations. Additionally, they filled out Patients' Attitudes and Beliefs Scale (PABS), Trust in Physician Scale (TPS) and Dermatology Life Quality Index (DLQI) questionnaires. Psoriasis Area Severity Index (PASI) was scored before and 3 months after treatment initiation. Results A total of 65 patients participated; 28% expected <90% clearance of psoriasis following treatment, whereas 72% expected 90%–100% clearance. No differences were found between bionaïve and non‐naïve patients. Mutually adjusted analysis showed that female gender (p = 0.026), higher PASI score (p = 0.004) and lower TPS score (p = 0.006) were associated with high overall expectations towards biological therapy. PABS scores were not significantly associated with high expectations. The proportion of patients having low expectations was greatest when asked about work/education, partner interaction and socializing. Additionally, high expectations towards these subjects were associated with higher DLQI (p = 0.047, p = 0.014 and p = 0.056, respectively). Patients with high overall expectations towards biological therapy had a significantly greater reduction in absolute PASI score following treatment (4.7 vs. 2.75), p = 0.048. Conclusions Techniques aimed at maximizing patients' expectation‐effect (placebo response) should be implemented in daily clinical practice. Knowledge about gender, disease severity, impact on life quality and patients' trust in physician should be taken into consideration.